Are systemic and topical tranexamic acid superior to each other in bleeding control in coronary bypass surgery? - Gözen, Füsun; Maltepe, Fikret (The European Research Journal, 2025)
Objectives: Tranexamic acid significantly reduces postoperative bleeding and transfusion requirements in cardiac surgery. Intravenous administration has been associated with thromboembolism and seizures. The complex protocols and serious side effects associated with this administration increase interest in intrapericardial administration, and its preferability is being reviewed. The purpose of this prospective, randomized, double-blind study was to compare the effects of intrapericardial tranexamic acid administered following cardiac surgery with those of intravenous administration on postoperative bleeding and possible complications. Methods: The study included 60 patients over the age of 18 who were undergoing elective coronary artery bypass grafting for the first time. The patients were randomized into intravenous and intrapericardial groups. Primary postoperative bleeding and transfusion requirements, and secondarily complications, reoperation and discharge times were evaluated. Results: The 60 coronary artery bypass grafting patients included in the study, consisting of 30 patients in intravenous and intrapericardial groups, were not different from each other in terms of demographic data and Euroscore parameters. Postoperative 24-hour chest tube drainage was measured as 890±551 mL in the intrapericardial group and 708±504 mL in the intravenous group. The similar drainage amounts detected in the two groups did not create a statistically significant difference (P=0.190). Transfusion requirements were similar in both groups. No complications developed in any patient and no reoperation was required due to bleeding. Conclusions: In conclusion; intrapericardial tranexamic acid application in coronary artery bypass grafting surgery reduces postoperative bleeding and transfusion requirement at an equivalent rate to intravenous. Intrapericardial application, which can provide the same effect without creating extra risk, may be a simpler and more practical method than systemic application, which includes complex protocols regarding dose and timing.